DESIGN AND FIELD VALIDATION OF A PHOTOVOLTAIC-POWERED WATER FLOW MONITORING SYSTEM FOR PUBLIC UTILITIES - Nenni Mona Aruan; Primasari Cahya Wardhani; Nurvita Cundaningsih; Autia Nurul Pujianti; Imelda Putri Alyah Rahmadani (Universitas Mataram, 2026)
The integration of renewable energy sources with sensor-based instrumentation offers a transformative approach to sustainable infrastructure, especially in water utility management. This study presents the development of a solar-powered autonomous water flow monitoring system deployed at the Lamongan municipal drinking-water utility (Perusahaan Daerah Air Minum; PDAM) in Indonesia. The system employs a 250 Wp photovoltaic (PV) module, coupled with an 18 V battery unit and a 10 A solar charge controller, enabling fully off-grid operation. A DC–DC buck converter maintains stable 50 V ± 2% regulation, supplying power to a calibrated flow sensor and a digital data acquisition unit, with an average power consumption of 0.5 W. Together, these components form a compact, self-sustaining instrumentation platform for real-time, continuous water flow monitoring. From the perspective of physics and instrumentation engineering, this research addresses the photovoltaic energy conversion process, electrical stability in DC power distribution, and flow signal conditioning under fluctuating solar irradiance. The flow sensor interface achieves an average accuracy of ±2% (2.08% with a coefficient of determination of 0.9984) over 1 to 20 Ls-1, supported by volumetric measurements. Long-term field operations over three months confirm stable system performance, with continuous data acquisition and negligible measurement drift, even under partial shading and low irradiance conditions. Power system monitoring indicates reliable energy autonomy with minimal interruption to sensor operation. The results demonstrate that the proposed system achieves accurate, stable, and energy-efficient real-time flow measurement without reliance on grid power. This study provides a validated instrumentation framework for renewable energy-powered sensing systems, enabling scalable deployment in smart water networks and other resource-monitoring applications.